Diktogloss as a methodological procedure for the implementation and development of communication skills - Рыспековa, Н. С. (Journal of Oriental Studies, 2017)
The problem of Japanese learners lies usually in the lack of the working knowledge of the language. Dictogloss is an activity to execute i+1 input and output. This paper clarifies the improvement of integrated competence such as grammar, listening, vocabulary and note-taking skills through dictogloss using the texts contains i+1 contents. To participate in peer-activities, learners become resources for each other, and which proved to contribute to cultivate learner autonomy.